The immunoregulatory role of monocytes and thrombomodulin in myelodysplastic neoplasms - Janssen, Luca L. G.; van Leeuwen-Kerkhoff, Nathalie; Westers, Theresia M.; de Gruijl, Tanja D.; van de Loosdrecht, Arjan A. (Frontiers in Oncology, 2024)
Myelodysplastic neoplasms (MDS) are clonal disorders of the myeloid lineage leading to peripheral blood cytopenias. Dysregulation of innate immunity is hypothesized to be a potent driver of MDS. A recent study revealed increased thrombomodulin (TM) expression on classical monocytes in MDS, which was associated with prolonged survival. TM is a receptor with immunoregulatory capacities, however, its exact role in MDS development remains to be elucidated. In this review we focus on normal monocyte biology and report on the involvement of monocytes in myeloid disease entities with a special focus on MDS. Furthermore, we delve into the current knowledge on TM and its function in monocytes in health and disease and explore the role of TM-expressing monocytes as driver, supporter or epiphenomenon in the MDS bone marrow environment.